UNA SEQUENZA PALINOLOGICA DI ETA' RUSCINIANA NEI SEDIMENTI LACUSTRI BASALI DEL BACINO DI AULLA-OLIVOLA (VAL DI MAGRA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Palynological investigations were carried out on the basal sediments of the Aulla-Olivola basin, precisely on the Aulla lacustrine deposit, which underlies by about 200 m, both stratigraphically and geometricall", the Olivola village, known for its famous Villafranchian fauna.This research has revealed;• a very rich palynoflora and a long, complex, vegetational succession. dominated by arboreal formations, with high abundance of exotic taxa, including also tropical-subtropical elements;• a climatic Sequence characterized by oscillations reflecting seasonality, especially in pluvial regime. A most evident climatic change occurs in the middle of the sequence.Moreover, the palynological sequence made it possible:• to assign the examined sequence to the Pliocene, because of the abundance of "Tertiary" elements (Taxodium-type, Sciadopitys, Sequoia-type, Nyssa, Palmae, etc.);• to-ascertain the rather archaic character of the Aulla pollenflora because of the significant occurrence Of pollen assemblages mainly confined to pre-Pliocene and early Pliocene (Symplocos, Sapotaceae, Clethraceae/Cyrillaceae-type, Magnolia-type, Sapindaceae- type, Sterculiaceae, cfr. Castanopsis, Tricolporopollenites sp. of archaic-type, etc.);• to compare the Aulla pollenflora with Other Pliocene pollen microfloras from Italy and Other areas and to evidence affinities and differences.From these comparisons it appears clearly that the Aulla lacustrine episode represents the most ancient continental Pliocene deposit discovered in Italy by means of pollen analyses so far. In fact, the palynological and climatic features indicate that the pollen sequence of Aulla is certainly older than the establishement of glacial/interglacial climatic cycles in the Northern Hemisphere (—2,5 Ma). Also the Villafranca d'Asti deposit (Early Villafranchian in age) is older than 2,5 Ma on the base of the paleomagnetic data. But the pollen floras of Villafranca d'Asti (Fornace R.D.B.) do not include the pre- Pliocene and early Pliocene elements, which characterize the Aulla pollen records.All these considerations lead to Suggest an older chronostratigraphic collocation of the Aulla sequence, most likely in a pre-Vilafranchian interval, i.e., in the Ruscinian stage interval. The large floristic affinities with the pollen zones of the Brunssumian of the Netherlands, entirely included in the Ruscinian stage, and also the pollen affinities with the continental middle-Pliocene western-alpine deposits support the chronostratigraphical assignation of the Aulla deposit to a (probably late) Ruscinian phase.Finally, the pollen record of Aulla represents a particular uniform floristic biozone, which is named here "Macrian" phase, easily distinguished from the contiguous vegetational biozones.The results reported above allow to extend the chronostratigraphic scheme of the paleofloristic evolution in Northern-Central Italy during the Pliocene.
Keywords: Palynology; Ruscinian; Villafranchian; Val di Magra; Northern Italy.